The Impact of Skills Development on Competitiveness: Empirical Evidence from a Cross-Country Analysis - Onsomu, Eldah Nyamoita; Ngware, Moses W.; Manda, Damiano K. (Education Policy Analysis Archives, 2010)
In the past half-century, most countries have emphasized the development of human capital as an instrument for economic growth, sustainable development, and improved global competitiveness. However, limited evidence exists on the link between skills development and a country's competitiveness. This paper examines the contribution and association of skills to a country's competitiveness. The study uses panel data from 84 countries in estimating an empirical model. Skills availability, foreign direct investments, secondary education, and technical (engineering) education and training are significant contributors to a country's competitiveness in a technologically changing and demanding world. This dynamic requires institutionalizing high-level technical skills development and on-the-job training programs in various firms that provided company specific and general skills to employees. The study recommends increased participation in secondary education and technically-oriented courses in tertiary education and programs that encourage skills transfer from foreign companies. Foreign direct investment, however, requires a conducive investment environment. Increased collaboration between tertiary institutions and industry is crucial for improved skilled development.